2020
DOI: 10.1002/pat.5110
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of biocompatible nano‐carrier based on Fe3O4 for magnetically hydroxychloroquine drug delivery

Abstract: In this work, we attempted to produce a new biocompatible nano‐carrier based on the Fe3O4 nanoparticles for drug delivery applications. The release profile of hydroxychloroquine (HCQ) was evaluated and the nano‐carrier was characterized using Fourier transform infrared, scanning electron microscope, energy dispersive X‐ray, X‐ray diffraction, thermogravimetric analysis, and vibration‐sample magnetometer. Specifically, maximum adsorption of HCQ was achieved in pH = 7, contact time 15 minutes, and environment te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…This novel formulation can increase HQC efficacy and safety by enhancing its lung exposure and half-life in lungs, while reducing its systemic exposure [ 34 ]. Another study, also evaluated the potential of magnetic delivery of HQC, by a Fe 3 O 4- -based biocompatible nanocarrier [ 35 ].…”
Section: Therapeutic Approaches In Covid-19mentioning
confidence: 99%
“…This novel formulation can increase HQC efficacy and safety by enhancing its lung exposure and half-life in lungs, while reducing its systemic exposure [ 34 ]. Another study, also evaluated the potential of magnetic delivery of HQC, by a Fe 3 O 4- -based biocompatible nanocarrier [ 35 ].…”
Section: Therapeutic Approaches In Covid-19mentioning
confidence: 99%
“…[215,[243][244][245] A vast number of promising nanocarrier-based antiviral treatments are currently under investigation to address the limitations of conventional therapy related to heterogeneous drug biodistribution and intracellular trafficking-cell-specific targeting and molecular transport to specific organelles. [246][247][248][249] In order to facilitate the development and clinical translation of all the most perspective solutions, in 2000 the U.S. National Science and Technology Council launched the National Nanotechnology Initiative and defined the greatest challenges regarding the application of nanoparticles in diagnostics and the treatment of infectious and civilization diseases.…”
Section: The Role Of Nanomedicine In Antiviral Therapiesmentioning
confidence: 99%
“…In addition, aerosol‐generating procedures such as nebulization should be performed very carefully in patients diagnosed with COVID‐19 due to the high risk of contagiousness through the respiratory system. [ 321 ] Sadr et al [ 246 ] synthesized a novel porous nanocarrier based on the magnetic Fe 3 O 4 nanoparticles, utilizing 3‐glycidoxypropyltrimethoxysilane as intermediate, and pectin biocompatible polymer for adsorption and release of hydroxychloroquine. It was shown that 32% of hydroxychloroquine was released from the vehicle surface within 90 min reaching 75% after 5 h in a simulated human blood environment (pH 7.4) at 37 °C.…”
Section: The Role Of Nanomedicine In Antiviral Therapiesmentioning
confidence: 99%
“…Magnetic nanocomposites are a new area of research on superparamagnetic nanomaterials for the targeted drug delivery using an external eld. Supermagnetic Fe 3 O 4 NPs can be an important component of magnetic nanocomposites due to properties such as targeted transfer, local hyperthermia treatment, and contrast enhancement for magnetic resonance imaging [9]. Hydrogels can be used as a second component of these nanocomposites, which can trap the drug in their network structure and release the drug due to the high water absorption [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Nano-carriers based on Fe 3 O 4 have also been used as a suitable carrier of this drug (for example Fe 3 O 4 @SiO 2 @GLYMO@pectin). Due to their good magnetic properties, they can deliver the drug to the desired location with an external magnetic eld [9]. In this project, hydrogel of poly vinyl alcohol (PVA) and tragacanth gum (TG) has been used for the targeted drug delivery system.…”
Section: Introductionmentioning
confidence: 99%